Strategic Design Skills in a Live Project: A Case Study of a Graduate Studio Course. - Mejía, G. Mauricio; Xie, Yumeng; Simeone, Luca; Tomlin, Stephanie (International Journal of Art & Design Education, 2025)
As design becomes more oriented towards strategy, services and systems, design learning is no longer something apprentices can develop only with masters' input and critique. Further, the experimentation and reflection commonly occurring inside studio‐based education is insufficient. Real‐world or live projects offer an alternative to learning strategic design skills and approaches such as design research, experience prototyping, visioning, co‐design or systems thinking. In this paper, we report a case study of a graduate studio live project exploring the use of strategic design skills. The findings suggest that students spend more time on and practice synthesis skills for research, reframing and dealing with uncertainty. They also develop skills for modelling and prototyping to address the need to improve communication with stakeholders. On the contrary, they underdevelop skills such as speculation, stakeholder facilitation and implementation viability. While live projects offer benefits, not all strategic design skills are equally used. Instructors' main role is to coach students and prepare them to interact with the client. Learning evaluation focuses not only on the process but also on the outcomes.